Shocks, uncertainty and regional resilience: The case of Brexit and Scottish SMEs. (November 2020) - Brown, Ross; Kalafsky, Ronald V; Mawson, Suzanne; Davies, Lori
Regional resilience is a topic of growing academic and policymaker interest. This article empirically examines this concept by scrutinising the impact of Brexit on Scottish small and medium-sized enterprises (SMEs). Given their crucial importance for the Scottish economy, SMEs are a good 'unit of analysis' and a powerful barometer for measuring regional resilience. The research adopted a novel mixed methods approach examining the Longitudinal Small Business Survey together with in-depth interviews with SMEs. It is clear from the survey analysis that certain types of SMEs (i.e. innovators and exporters) were disproportionately fearful of Brexit. This was firmly corroborated by the interview data which found these same firms to be the most detrimentally impacted, manifesting in reductions in employment, exports and innovation. In contrast, the majority of domestically focused, less innovative SMEs were much less concerned and less negatively affected. While a small minority managed to deploy adjustment mechanisms to mitigate these negative effects, overall many firms had major difficulties operationally and strategically coping with this uncertain and turbulent environment. The findings suggest proactive public policies will be needed to help mitigate the difficulties caused by Brexit for certain types of SMEs.